Perioperative manometric studies in laparoscopic Watson’s repair versus Nissen’s fundoplication - Abdelshahid, Moharam; Ammar, Mohammed Sabry; Nassar, Mohammed Nazeeh Shaker (International Surgery Journal, 2018)
Background: Hiatus Hernia (HH) and GERD are common upper gastroesophageal disorders, The Nissen`s fundoplication is one of the most effective and commonly used surgical techniques in management of both GERD and hiatus hernia (HH). many surgeons are searching for alternative procedures due to the mechanical obstructive effects of Nissen’s fundoplication, one of these procedures is partial anterior fundoplication (Watson’s repair). Methods: Eighty two patients, diagnosed to have GERD and/or HH, were scheduled for present study for laparoscopic anti-reflux surgery. They were randomized to either Watson’s repair (anterior partial fundoplication) (group I) or Nissen repair (group II) in the period between June 2012 and March 2017. Forty two patients for group I and forty patients were included in group II. Group I had partial anterior fundoplication and group II had Nissen’s fundoplication. Follow up for all patients included in our study was scheduled at (2, 4weeks and 3, 6, 12months postoperatively) both subjectively - using a standardized scoring system for reflux symptoms (heartburn, regurgitation and dysphagia), gas bloating and objectively-using esophago-gastroscopy at 6ms and 12ms postoperatively, esophageal manometry, 24hours PH monitoring at 6ms and 12ms post operatively. Results: Three cases were excluded from the study because they were converted to open procedure, one of group I and two of group II. Mean operative time was significantly shorter in group I. As regarding to reflux symptoms (heartburn and regurgitation) Nissen was significantly higher in control of reflux symptoms at 3months but at 6, 12months Nissen still higher but without a clear significant difference. On the opposite side dysphagia was significantly higher in Nissen group than in Watson group at 3months and remained higher at 6,12months but with no significant difference, also gas related symptoms were higher in Nissen group than in Watson group all the time of follow up. Objectively, esophagitis improved to a similar extent in both groups. Watson was less effective in improving LES characters, and 24hours PH parameters in comparison to Nissen group but without any significant difference in both groups. Conclusions: Partial anterior fundoplication (Watson repair) can be safe, effective and simple alternative procedure for Nissen’s fundoplication with less obstructive symptoms and complications.